Oral Hedgehog Pathway Inhibition as a Means for Ocular Salvage in Locally Advanced Intraorbital Basal Cell Carcinoma. Issue 1 (January 2019) - Mathis, Jason; Doerr, Timothy; Lin, Edward; Ibrahim, Sherrif F.
Abstract : BACKGROUND: Basal cell cancer is the most common cutaneous malignancy. It rarely presents with locally advanced or metastatic disease. Rare presentations such as intraorbital invasion remain a difficult clinical problem with significant potential morbidity. There is no review of sonic hedgehog pathway inhibitors (HPIs) for intraorbital basal cell cancer, and evidence regarding optimal management is limited. OBJECTIVE: To evaluate the evidence for the management of intraorbital basal cell cancer with HPIs. METHODS: A search to identify evidence for treatment intraorbital basal cell cancers with HPIs to date was performed in PubMed database and OVID using the phrases "basal cell cancer/carcinoma/BCC, " "intraorbital, " "orbital, " "ocular, " "periocular, " "vismodegib, " "GDC-0449, " "sonidegib, " and "LDE224, " in various combinations with Boolean operators "AND" and "OR." RESULTS: Rigorous clinical trials have previously reported the use of vismodegib and sonidegib in locally advanced and metastatic basal cell carcinoma (BCC). However, specific descriptions of treatment of intraorbital tumors are rarely presented in detail adequate for analysis. Twenty-two cases of intraorbital BCC treated with vismodegib have been described in the literature, and no cases using sonidegib were identified. These vary in quality, but highlight important questions regarding optimal treatment duration, follow-up, and adjunctive therapies. Reports describing locally advanced BCC in various facial and periocular locations, but without specific mention of intraorbital invasion, were excluded. CONCLUSION: Vismodegib is an attractive eye and vision-sparing option in patients with locally advanced intraorbital basal cell cancer whose other options often include exenteration, radiation, or other radical surgery.